CENTRALISATION OF POWERS OF PUBLIC ADMINISTRATION ENTITIES UNDER MARTIAL LAW AS A GUARANTEE OF ECONOMIC AND LEGAL STABILITY OF THE STATE FUNCTIONING - Roman Stefanchishen; Andrii Ihnatiev; Olena Pasechnyk (Baltic Journal of Economic Studies)
The subject of the study is the impact of the concept of centralisation of powers among public administration bodies under martial law conditions as a prerequisite for ensuring national security in general and economic security in particular. Methodology. The research was conducted using general and specific scientific methods of cognition. The comparative method was used to identify changes in the status of the activities of public administration bodies under martial law. The quantitative and qualitative parameters characterising the peculiarities of the application of certain measures of the martial law regime were determined by means of analysis. The results of the study indicate that there is an immediate need for authorised entities in Ukraine to modify their activities in order to enhance and adapt the existing measures to the conditions of martial law. It has been determined that the powers of the President of Ukraine and military administrations in the field of economic security, which are applied during the legal regime of martial law, must be revised. Conclusion. The authors establish that under martial law, the President of Ukraine, the National Security and Defence Council and military administrations are vested with a wide range of powers, including those which directly affect economic relations at the State and municipal levels. The paper presents a proposal to amend the current legislation with a view to clarifying the powers of military administrations, which will ultimately facilitate their compliance with the fundamental principles of state regulation. The role of the National Security and Defence Council is defined as an institution that identifies national security risks (including financial and economic ones) and develops strategies to reduce their latency.